Delayed vs. early enteral feeding after repair of congenital recto-vestibular fistula: The effect on perineal wound healing - Kurdi, Mazen; Moukhtar, Ahmed; Elkholy, Mahmoud; Alwassia, Heidi; Bamehriz, Maha; Khirallah, Mohammad Gharieb (Frontiers in Pediatrics, 2023)
Introduction: congenital Recto vestibular fistula represents the commonest type of anorectal malformation in females. The treatment of this anomaly is mainly approached either through anterior or posterior sagittal ano-rectoplasty approach. Several perioperative factors may affect the outcome. One of major postoperative complications is the occurrence of wound infection. We aimed to study the effect of delayed vs early enteral feeding on the occurrence of perineal wound infection (PWI) after repair of congenital recto vestibular fistula. Patients and methods: Fifty-five infants with recto-vestibular fistula were included. They were managed by single stage anterior sagittal anorectoplasty (ASARP)at an age ≥ 3 months. Groups A and B included infants who started oral intake on the 6th and 2nd postoperative days respectively. Group A infants were kept on peripheral parenteral nutrition (PPN) during the fasting period. Results: Superficial wound infection occurred in three cases in group A while it developed in seven cases in group B. Deep perineal infection occurred in two and five cases in group A and group B respectively. The mean hospital stay was 8 days in group A vs 13 days in group B when PWI developed. Conclusion: Delayed enteral feeding with PPN keeps the perineal wound less contaminated with stool. This promoted proper and fast healing with lower incidence of PWI. Also, PPN compensates the catabolic effects of both surgical trauma and fasting during the postoperative period and ensures maintenance of normal levels of essential nutrients that allow for proper healing.